PENGARUH BERITA TOLERANSI BERAGAMA DI MEDIA ONLINE TERHADAP SIKAP TOLERANSI SISWA KELAS 3 SMA DI PEKANBARU - Paramitha, Suha; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
A good attitude and understanding of religious tolerance in adolescents will foster a good attitude of tolerance as adults. The theory used in this study is the theory of TRA (Theory of Reasoned Action) and the theory of S-O-R (Stimulus-Organism-Response). The purpose of this study was to determine the effect of news on religious tolerance in online media on the tolerance attitude of class III students in Pekanbaru.This study uses quantitative experimental research methods, with data collection techniques, namely through questionnaires. The population in this study amounted to 529 students with a sample of 84 respondents using the random sampling method. The data analysis method used is simple linear regression analysis. Data processing is carried out with the SPSS version 23 program.The results obtained from a simple linear regression analysis in this study is that there is a news effect of religious tolerance in online media on the tolerance attitude of class III students in Pekanbaru at 0.05 which means that religious tolerance has an influence on tolerance with a positive relationship due to coefficient amounting to 0.430. The results of this study also explain the contribution of variation from the independent variable, namely the news of religious tolerance to the dependent variable, namely the attitude of tolerance of 0.140 or 14%. While the contribution of other independent variations that can explain the dependent variable is 86% excluding the variables used in this study.